Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.2967/jnmt.121.263135
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Dose to Medical Staff from Administering177Lu-PSMA-DKFZ-617 Therapy

Abstract: The number of radioligand therapy applications for metastatic castration-resistant prostate cancer has been continuously rising in most nuclear medicine departments in Iran, but to our knowledge, no one has studied the dose to staff who perform treatment procedures. The current study aimed to determine the external radiation dose received by staff who, using or not using a lead shield, treat patients with 177 Lu-prostate-specific membrane antigen therapy. Methods: This study used a personal thermoluminescent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Other studies also show similar values (0.36 ± 0.16 µSv/GBq (26) and 0.24 ± 0.05 µSv/GBq ( 14)), although no information is given on the use of aprons. A study involving administration of 177 Lu-PSMA-617 obtained 0.60 ± 0.05 µSv/GBq for physicians behind a lead shield (45). On the other hand, in a previous study on effective doses during manipulation of 68 Ga-DOTATOC (46) it was concluded that electronic dosemeters could underestimate the dose due to the non-linear response of the Geiger-Müller detector at the 68 Ga photon energies (1077 keV) and the pure beta eld.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also show similar values (0.36 ± 0.16 µSv/GBq (26) and 0.24 ± 0.05 µSv/GBq ( 14)), although no information is given on the use of aprons. A study involving administration of 177 Lu-PSMA-617 obtained 0.60 ± 0.05 µSv/GBq for physicians behind a lead shield (45). On the other hand, in a previous study on effective doses during manipulation of 68 Ga-DOTATOC (46) it was concluded that electronic dosemeters could underestimate the dose due to the non-linear response of the Geiger-Müller detector at the 68 Ga photon energies (1077 keV) and the pure beta eld.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have been conducted to investigate the extracorporeal radiation levels of patients undergoing 177 Lu-PSMA therapy through field measurements (Demir et al 2016, Abuqbeitah et al 2018, Kurth et al 2018, Mair et al 2018, Rantala et al 2018, Mahmoudi et al 2023, Parlak et al 2023, and the dose rate limits have also been proposed for the patient's release in Europe and other countries (Bakker et al 2006, IAEA 2009, 2014, ICRP 2012, Turner 2012, Calais and Turner 2014, Lawal et al 2019. Nevertheless, all the limits were set at the distance of 1 m from the patient, the dose rates at other distances are still not clear.…”
Section: Introductionmentioning
confidence: 99%